PENGARUH UMUR PERUSAHAAN, UKURAN PERUSAHAAN, REPUTASI AUDITOR, DAN PERGANTIAN AUDITOR TERHADAP AUDIT REPORT LAG - Shinta Widhiasari, Ni Made; Budiartha, I Ketut (E-Jurnal Akuntansi, 2016)
Audit report lag is the time span of audit settlements from company's closing date to the date that is listed in the audit report. Bapepam requires each of go public companies to publish its annual report no later than four months after the fiscal year ends. The aim of this study was to determine the effect of company’s age, size of company, the reputation of the auditors, and auditor switching to audit report lag in manufacturing companies listed on the Indonesia Stock Exchange during the period of 2012-2014. As many as 102 samples were obtained through purposive sampling technique. The data analysis technique used was MRA. The results suggested that the company’s age gave positive and significant effect to the audit report lag, while company size, auditor's reputation, and auditor switching didn’t affect the auditor's audit report lag.
Keywords: audit report lag, company age, company size, auditor reputations, auditor switching